INVASIVE CERVICAL RESORPTION DUE TO IONTOPHORETIC INTERNAL BLEACHING WITH HYDROGEN PEROXIDE: TWO CASE REPORTS - Yaneta Kouzmanova (Peytchinski Publishing, 2022)
Background: Invasive cervical resorption is a localised inflammatory-mediated aggressive form of an external root resorptive process of the tooth. One of the predisposing factors associated with ICR is the internal bleaching of non-vital teeth. The maxillary anterior teeth are highly affected among all tooth types. Case reports: The clinical management and one-year follow-up results of two cases with invasive cervical resorption in maxillary central incisors due to iontophoretic internal whitening with 30% hydrogen peroxide are presented in this study. The complications associated with post-bleaching ICR as well the prevalence and underlying mechanism of this phenomenon and treatment planning, are discussed. Conclusion: Clinicians should be alert to the possibility of ICR, especially following iontophoretic non-vital bleaching. A combined multidisciplinary treatment approach can be applied based on thorough clinical, radiographical and CBCT evaluation.